Bad moonlight - Stine, R. L. (New York : Pocket Books, 1995)
Danielle is excited about being picked to be the band's lead singer until one member is killed by a werewolf.
"An Archway paperback."
"A Parachute Press book."
IL 7+
Accelerated Reader AR
Keywords: Horror tales; Horror fiction; Horror fiction